1990
DOI: 10.1103/physrevlett.64.200
|View full text |Cite
|
Sign up to set email alerts
|

Real-space atomic structure of a two-dimensional decagonal quasicrystal

Abstract: We have imaged for the first time the atomic structure of a quasicrystal using a scanning tunneling microscope. The structure of the decagonal AI65C020CU15 quasicrystal is described by a pentagoncenter-decorated pentagonal quasilattice giving strong evidence for a tiling model. The scanningtunneling-microscope measurements of the surface are in good agreement with the high-resolution xray-diffraction measurements of the bulk.PACS numbers: 61.50. Em, 61.55.Hg, 63.90.+t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…A first report on the structure of the 10-fold AlÀCuÀCo surface concluded that it is bulk terminated. 22 The same surface has been reinvestigated recently using different techniques, and it was concluded that the top surface layer is Al enriched compared to the bulk composition. 23 Nevertheless, STM images show geometrical features consistent with a truncated bulk structure, with 2 nm clusters decorating the nodes of a decagonal tiling.…”
Section: Resultsmentioning
confidence: 99%
“…A first report on the structure of the 10-fold AlÀCuÀCo surface concluded that it is bulk terminated. 22 The same surface has been reinvestigated recently using different techniques, and it was concluded that the top surface layer is Al enriched compared to the bulk composition. 23 Nevertheless, STM images show geometrical features consistent with a truncated bulk structure, with 2 nm clusters decorating the nodes of a decagonal tiling.…”
Section: Resultsmentioning
confidence: 99%
“…More then ten years ago, the discovery that centimetre size samples of decagonal d -AlCuCo and icosahedral iAlPdMn could be grown opened up the possibility of surface studies of these quasicrystals 1 . Since then other quasicrystal samples have been grown to similar dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the elements at the surface of a decagonal quasicrystalline Al-Co-Cu alloy could be identified by Becker and coworkers using arguments based upon stoichiometry -4-more complicated icosohedral quasicrystalline alloy structure [24]. More recently, other surface atoms, Pt and Ni have been differentiated in the surface layers of solid alloys with known surface compositions, but only under special STM tip conditions that could not be reproduced at will [25].…”
Section: Contrast In Stm Imagingmentioning
confidence: 99%